Melanocyte-dependent macrophage redistribution enhances skin immunity upon acute stress - Erin Faught; Marcel J. M. Schaaf (Proceedings of the National Academy of Sciences, 2025)
It is well established that stress generally suppresses immunity. However, under certain conditions, acute stress has been shown to stimulate the immune system, particularly those at barrier surfaces like the skin. The cellular and molecular mechanisms underlying this effect remain poorly understood. In the present study, we have identified an immune-enhancing effect of stress using zebrafish larvae. The use of this animal model allowed us to visualize the redistribution of macrophages to the skin upon exposure to an acute stressor, which appeared to be dependent on the increased levels of cortisol. Through real-time imaging of fluorescently labeled leukocytes, we observed that this cortisol-driven redistribution was mediated by both the mineralocorticoid and the glucocorticoid receptor, which upregulated the chemokine receptor Cxcr4. Strikingly, this stress-induced macrophage migration required the presence of melanocytes in the skin, which increased the expression of the gene encoding Cxcl12, the ligand for Cxcr4. This result indicates a pivotal role for pigment cells in immune regulation under stress. Functional assays further revealed that the redistributed macrophages actively increased antigen uptake from the external environment, suggesting an elevated state of immune readiness. Together, we demonstrate that acute stress triggers a coordinated, cortisol-mediated response that enhances immune surveillance at the skin barrier. This stress-induced enhancement of barrier immunity potentially prepares the organism for increased pathogen exposure under challenging conditions.